Arab Parents' Involvement in School Reform in Israel. Issue 2 (April 2014) - Arar, Khalid; Abu-Asbah, Khaled; Nasra, Muhammed Abu
Current research indicates that parental involvement positively influences children's academic success. This study investigates parental involvement in the Arab education system in Israel, highlighting involvement in the New Horizon reform. We interviewed school principals and parent committee chairpersons from 15 Arab schools. The study confirmed recognized parent involvement patterns in schools: First, schools avoid involving parents, thereby limiting participation to material assistance. Second, schools view parents as a threat. Third, parents feel that schools promote academic achievement rather than education. We suggest paths to encourage meaningful parent involvement to improve the Arab education system in Israel, relevant also to educators in other developing societies.